Influenza and ARVI: challenges and solutions - Article Editorial (Медицинский совет, 2019)
ARVI and influenza are one of the topical problems of pediatrics, which is due to the high level of morbidity in the child population, a significant incidence of severe and complicated forms of disease, especially in young children. In the structure of infectious pathology in children, this group of diseases still retains its leading position, accounting for up to 70% of all registered cases. Almost every child annually and more than once endures ARVI or flu episodes. This group of infections causes significant economic damage both to the household budget and the national budget as a whole. In order to improve the provision of medical care for children, improve the qualifications of pediatricians and share experience of the Department of Pediatrics named after Academician G.N. Speranskiy RMACPE (Head of Department Dr. of Sci. (Med), Professor I.N. Zakharova), a scientific and practical seminar «Influenza and acute respiratory infections 2018/2019: challenges and solutions» was held. Within the framework of the event, supported by «Valenta Pharm», specialists considered a number of topical issues, including vaccine prophylaxis and treatment of ARVI and influenza, taking into account modern epidemiological, microbiological and virological data. The seminar participants paid special attention to the validity of antiviral therapy in children, in particular, such drug as Ingavirin®.